The effects of NutraGen supplement on cattle growth performance, energetic efficiency, carcass characteristics, and characteristics of digestion in calf-fed Holstein steers - Carvalho, Pedro H. V.; Latack, Brooke C.; Ferraz Junior, Marcos V. C.; Flores, Ruben; Sanchez-Cruz, Gerson; Montaño, Martin F.; Zinn, Richard A. (Frontiers in Veterinary Science, 2023)
Evaluation of the effects of feeding NutraGen supplement (NTG; Phibro Animal Health, Teaneck, NJ, USA) on growth performance, energetic efficiency, carcass characteristcs, and characteristics of digestion in calf-fed Holstein steers fed a conventional growing-finishing diet. Trial 1 evaluated growth performance, dietary energetics and carcass characteristics. 200 Holstein steer calves (134 ± 5 kg) were blocked by initial body weight (BW) and randomly assigned to 40 pens (5 steers/pen). Dietary treatments consisted of a steam-flaked corn-based growing-finishing diet supplemented with 0, 0.2, 0.4, or 0.6% NTG (DM basis). In trial 2, four Holstein steers (170 ±6 kg) with cannulas in the rumen and proximal duodenum were used in a 4 × 4 Latin square experiment to evaluate digestibility and ruminal characteristics using the treatments from trial 1. Compared to non-supplemented cattle, NTG increased BW (2.0%, P = 0.02) and tended to increase ADG (3.6%, P = 0.07) during the initial 56 d period. However, there were no treatment effects on overall growth performance and efficiency of dietary energy utilization (P > 0.10). Supplementation of NTG increased (linear effect; P ≤ 0.03) longissimus muscle area and kidney, pelvic, and heart fat. There was no effect (P ≥ 0.05) of NTG supplementation on other carcass characteristics, liver abscess incidence, or liver abscess scars. Supplementation decreased the molar proportion of ruminal propionate (P = 0.05) and tended to increase acetate:propionate molar ratio (P = 0.09). However, there was no effect of NTG supplementation on ruminal and total tract diet digestion. NTG increased performance of Holstein steers during the first 56 d on feed in the feedlot. In addition, the steers had an increase in KPH fat and LM area, indicating that the additive induced change in metabolism of the steers.